Light-emitting thin-film field-effect transistors - Stallinga, Peter; Gomes, Henrique L. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
A model for thin-film field-effect transistors in which the active layer is treated as purely two-dimensional is applied to ambipolar devices that have shown to be light emitting. This results in an adequate description of the electrical characteristics.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 373-380
Keywords: optyka; thin-film transistors; ambipolar; organic materials; amorphous silicon; two-dimensional electronics